(untitled) (Research, Society and Development, 2020)
The aim of this study was to find out the specific time when people are more vulnerable to temperature variations during their daily life. Modeling by daily stratified analysis was performed to morbidity for the total population and for subgroups of elderly and young using Poisson distribution. We found that the temperature during the day is more associated with morbidity / mortality daily. The relative risk estimates and magnitude of associations arising from time to temperature measurements in time are similar or even stronger compared to those modeled by the daily statistics. This phenomenon remains true to the lagged hourly temperature measurements and changes in standards from January to December associations. People are more vulnerable to temperature changes in the early morning around 5 and 8 AM and night around 8 PM.